PENGARUH WORK LIFE BALANCE DAN KEPUASAN KERJA TERHADAP LOYALITAS KERJA KARYAWAN DI DINAS SOSIAL KOTA DENPASAR - NI PUTU WIDIASTUTI; HISAM ABDILLAH BAIHAKI (Universitas Mahasaraswati K. Mataram, 2023)
This study aims to determine: (1) The effect of work life balance on employee loyalty at the Denpasar City Social Service, (2) The effect of job satisfaction on employee work loyalty at the Denpasar City Social Service. This research is a descriptive analysis research using a quantitative approach. Data collection using observation, documentation and questionnaires. The sample in this study was 91 people and used the random sampling method. The validity test used Cronbach's Alpha. Data analysis using multiple linear regression. The results of the study found that: (1) Work life balance has a positive and significant effect on employee work loyalty, the sig value is obtained. 0.042 <α 0.005 indicates that H0 is rejected and H1 is rejected. (2) Job satisfaction has a positive and significant effect on employee loyalty, a Sig.t value of 0.000 <0.05 indicates that H0 is rejected and H1 is accepted. The simultaneous contribution or contribution of work life balance and job satisfaction variables to employee loyalty is 63.8% while 36.2% is determined by other variables not examined in this study.